1995
DOI: 10.1111/j.1748-1716.1995.tb09914.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle metabolism during short duration high‐intensity exercise: influence of creatine supplementation

Abstract: Seven male subjects performed repeated bouts of high-intensity exercise, on a cycle ergometer, before and after 6 d of creatine supplementation (20 g Cr H2O day-1). The exercise protocol consisted of five 6-s exercise periods performed at a fixed exercise intensity, interspersed with 30-s recovery periods (Part I), followed (40 s later) by one 10 s exercise period (Part II) where the ability to maintain power output was evaluated. Muscle biopsies were taken from m. vastus lateralis at rest, and immediately aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
158
6
17

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(198 citation statements)
references
References 23 publications
17
158
6
17
Order By: Relevance
“…Possibly, the differences in total muscles mass involved during kayaking compared to wheelchair racing seemed to be of higher impact than expected and might be responsible for the reported discrepancies concerning an ergogenic effect. Moreover, lactate concentrations were not influenced by creatine supplementation in the present study, which supports the hypothesis that the glycolytic pathways were unaltered by creatine supplementation as proposed by Birch et al 2 Many studies in the past reported positive effects on performance of different types and durations after a short-term creatine supplementation, [1][2][3][4][5][6][7][8]21 whereas others found no effect. 16,[22][23][24][25][26] Interestingly, in most of the studies showing no ergogenic effect on exercise performance after creatine supplementation, a time or distance trial was performed, [22][23][24][25][26] whereas in studies with a positive effect the time to exhaustion at a given workload was determined.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Possibly, the differences in total muscles mass involved during kayaking compared to wheelchair racing seemed to be of higher impact than expected and might be responsible for the reported discrepancies concerning an ergogenic effect. Moreover, lactate concentrations were not influenced by creatine supplementation in the present study, which supports the hypothesis that the glycolytic pathways were unaltered by creatine supplementation as proposed by Birch et al 2 Many studies in the past reported positive effects on performance of different types and durations after a short-term creatine supplementation, [1][2][3][4][5][6][7][8]21 whereas others found no effect. 16,[22][23][24][25][26] Interestingly, in most of the studies showing no ergogenic effect on exercise performance after creatine supplementation, a time or distance trial was performed, [22][23][24][25][26] whereas in studies with a positive effect the time to exhaustion at a given workload was determined.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies investigated the influence of creatine supplementation on leg muscle performance. [1][2][3][4][5][6]8,9,16,[24][25][26] Since arm muscles contain more type II fibres than leg muscles and since type II fibres have initially a higher phosphocreatine content than type I fibres, 15 it could be hypothesised that creatine supplementation would be less efficient for arm exercise, an assumption that is supported by our findings. However, this hypotesis has to be investigated in further studies, as one cannot conclude definitely if an initially higher phosphocreatine content of arm muscles limits the effectiveness of a creatine supplementation in this muscle group.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Aside from dehydration-related fatigue, which has been firmly established [11,12], other proposed possible mechanisms focus on fluctuations in glycogen, creatine phosphate (CP), potassium, and blood lactate, but the findings have been conflicting and no single factor has been definitively linked to fatigue [5,[13][14][15][16][17][18]. There has also been increasing support for the role of the CNS and psychological factors such as motivation, experience, routines, self-belief, and perception of exertion/recovery [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%